Kajian administratif resep pada pasien rawat jalan di instalasi farmasi rumah sakit x Di kota Tangerang Selatan - Fadhilah, Humaira; Anggraini, Monika Sari; Andriati, Riris (JOURNAL OF Pharmacy and Tropical Issues, 2024)
Background:Prescription service begins with a prescription screening process that can be seen from 3 aspects of prescription completeness which include administrative requirements, clinical requirements, and pharmaceutical requirements. The administrative aspect was chosen because it is the initial stage in the prescription screening process when the prescription is presented at the pharmacy because it includes all the information in the prescription related to the clarity of drug writing, prescription validity, and clarity. from the information in the recipe. Purpose: To see the percentage of prescription administration completeness in outpatients at IFRS X for the period October-December 2018. Methods: Using a descriptive design and sampling method using random sampling method, in order to obtain a sample of 390 prescription sheets. Sampling was carried out by observing all incoming outpatient prescriptions during the October-December 2018 period. Administrative screening was carried out on 390 outpatient prescription sheets by filling out a data collection table (check list) in accordance with the aspects of prescription completeness being reviewed. Results: Completeness of prescribing based on patient data, including: patient's name 100%, patient age 89.2%, gender 100%, weight 13.1%, and patient address 93.3% and completeness of prescription based on doctor's legality, including : 100% doctor's letter name, No.100% doctor's SIP, 100% doctor's address, 100% doctor's telephone number, 100% doctor's initials, and 100% date of prescription, while incompleteness based on patient data includes; 0% patient name, patient age 10.8%, gender 0%, weight 86.9%, and patient address 6.7%, and incompleteness based on doctor's legality include; 0% doctor's name, 0% SIP No, 0% doctor's address, 0% doctor's phone number, 0% doctor's initials, and 0% prescription date. Conclusion: In this case, the completeness of prescription administration on outpatient prescriptions at RSU X is declared to have not fulfilled the prescription administration aspect based on the Regulation of the Minister of Health Number 58 of 2014. Keywords: Administrative Sciences; Recipe; Patient; outpatient Pendahuluan: Dalam pelayanan resep didahului dengan proses skrining resep yang dapat dilihat dari 3 aspek kelengkapan resep yang mencakup persyaratan administratif, persyaratan klinis, persyaratan farmasetik. Aspek administratif dipilih karena merupakan tahap awal dalam proses skrining resep pada saat resep dilayani diapotek karena mencakup seluruh informasi didalam resep yang berkaitan dengan kejelasan tulisan obat, keabsahan resep, dan kejelasan informasi didalam resep. Tujuan: Untuk melihat persentase kelengkapan administratif resep pada pasien rawat jalan di IFRS X pada periode oktober-desember 2018. Metode: Menggunakan rancangan deskriptif dan metode pengambilan sampel menggunakan metode random sampling, sehingga didapatkan sampel sebanyak 390 lembar resep. Pengambilan sampel dilakukan dengan mengamati seluruh resep pasien rawat jalan yang masuk selama periode oktober-desember 2018. Dilakukan skrining administratif terhadap 390 lembar resep pasien rawat jalan dengan mengisi tabel pengambilan data (Check list) sesuai dengan aspek kelengkapan resep yang ditinjau. Hasil: Kelengkapan administrasi resep berdasarkan data pasien, meliputi: nama pasien 100%, usia pasien 89,2%, jenis kelamin 100%, berat badan 13,1%, dan alamat pasien 93,3% dan kelengkapan resep berdasarkan legalitas dokter, meliputi: nama dokter 100%, No. SIP dokter 100%, alamat dokter 100%, no telp dokter 100%, paraf dokter 100%, dan tanggal penulisan resep 100%, sedangkan ketidaklengkapan berdasarkan data pasien meliputi; nama pasien 0%, usia pasien 10,8%, jenis kelamin 0%, berat badan 86,9%, dan alamat pasien 6,7%, dan ketidaklengakapan berdasarkan legalitas dokter meliputi; nama dokter 0%, No SIP 0%, alamat dokter 0%, no telpon dokter 0%, paraf dokter 0%, dan tanggal penulisan resep 0%. Simpulan: Dalam hal ini kelengkapan resep secara administratif pada resep pasien rawat jalan di RSU X dinyatakan belum memenuhi aspek administratif resep berdasarkan Permenkes RI No. 58 tahun 2014. Kata Kunci: Kajian Administratif; Resep; Pasien; Rawat Jalan